Simulation process templates for e-business modelling. (31st August 2005) - Albores, Pavel; Ball, Peter; MacBryde, Jillian
This paper argues the use of reusable simulation templates as a tool that can help to predict the effect of e-business introduction on business processes. First, a set of requirements for e-business modelling is introduced and modelling options described. Traditional business process mapping techniques are examined as a way of identifying potential changes. Whilst paper-based process mapping may not highlight significant differences between traditional and e-business processes, simulation does allow the real effects of e-business to be identified. Simulation has the advantage of capturing the dynamic characteristics of the process, thus reflecting more accurately the changes in behaviour. This paper shows the value of using generic process maps as a starting point for collecting the data that is needed to build the simulation and proposes the use of reusable templates/components for the speedier building of e-business simulation models.